2010
DOI: 10.1111/j.1559-1816.2010.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

The Asceticism Dimension of the Protestant Work Ethic: Shedding Its Status of Invisibility

Abstract: Asceticism seems an “invisible” Protestant work ethic (PWE) dimension that has largely been ignored in research. This study, building directly on existing knowledge, investigated the possibility that deference to authority was central to asceticism and the possible ethical implications of this. In 3 samples of employed persons, results demonstrated that highly ascetic individuals were highly authoritarian, were low in advanced moral reasoning, and regarded ethically questionable activities benefiting organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…Most published studies use three stories and the revised DIT has five. Approximately 2 weeks later, participants received a second survey containing, in addition to other measures not relevant here (see Mudrack, 2007; Mudrack & Mason, 2010), the 20-item Mach IV scale of Christie and Geis (1970) designed to assess Machiavellian (Mach) tendencies (α = .77; for example, “Anyone who completely trusts anyone else is asking for trouble”) and the 30-item Right-Wing Authoritarianism (RWA) Scale of Altemeyer (1988; α = .88; for example, “Obedience and respect for authority are the most important virtues children should learn”) that appeared in a 7-point response format, with strongly disagree (1 point) and strongly agree (7 points) as end points. Mach scores could thus range from 20 to 140, and RWA scores could range from 30 to 210.…”
Section: Methodsmentioning
confidence: 99%
“…Most published studies use three stories and the revised DIT has five. Approximately 2 weeks later, participants received a second survey containing, in addition to other measures not relevant here (see Mudrack, 2007; Mudrack & Mason, 2010), the 20-item Mach IV scale of Christie and Geis (1970) designed to assess Machiavellian (Mach) tendencies (α = .77; for example, “Anyone who completely trusts anyone else is asking for trouble”) and the 30-item Right-Wing Authoritarianism (RWA) Scale of Altemeyer (1988; α = .88; for example, “Obedience and respect for authority are the most important virtues children should learn”) that appeared in a 7-point response format, with strongly disagree (1 point) and strongly agree (7 points) as end points. Mach scores could thus range from 20 to 140, and RWA scores could range from 30 to 210.…”
Section: Methodsmentioning
confidence: 99%
“…Asceticism would involve self‐denial, austerity, self‐discipline, and a tendency to refrain from self‐indulgence and selfishness (Mudrack & Mason, 2010). Ascetic persons with these values would be inclined to control their impulses to act inappropriately toward an organization.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Ascetic persons with these values would be inclined to control their impulses to act inappropriately toward an organization. In addition, researchers thought that the high personal ethical standards are implicitly associated with asceticism (Mudrack & Mason, 2010), so ascetic employees are unlikely to approve ethically dubious activities, such as stealing from their organizations. Similarly, it is nearly impossible that ascetic employees are tempted to conduct CWBs.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research, however, has suggested that other dimensions of the Protestant work ethic 156 CCM 22,1 scale are worth examining. Specifically, Mudrak and Mason (2010) find that asceticism merits attention as a distinct component of work ethic to examine the extent to which individuals defer to authority. Additionally, we also look forward to future research aimed at influencing work ethic.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%